E-Customer Relationship Management on Satisfaction of Millenial Zakat Users in Lampung Province (Equilibrium: Jurnal Ekonomi Syariah, 2025)
This study aims to analyze how the e-CRM feature affects muzakki (zakat payers) satisfaction and whether satisfaction contributes to loyalty behaviour in the context of collecting zakat, infaq, and non-profit alms. In addition, this study also included religiosity variables that are considered to moderate the relationship between e-CRM and loyalty behaviour as novelty. This study used a quantitative survey method. This study focuses on 500 millennial zakat payers in Lampung Province who utilize digital platforms for zakat payments, selected through purposive sampling to ensure a representative sample. The collected data was processed and analysed using Structural Equation Modeling (SEM) with LISREL. The findings of this study reveal that e-CRM on digital zakat platforms significantly increases muzakki satisfaction, but its impact on loyalty behavior remains low. The study identified that the pre-payment, during payment, and post-payment dimensions of e-CRM contribute to user convenience and service responsiveness, leading to higher satisfaction. However, muzakkis do not consistently use digital platforms for repeated zakat payments, indicating a gap between satisfaction and loyalty. In addition, religiosity strengthens the link between e-CRM and loyalty, but low zakat literacy remains a major challenge, preventing muzakki from fully embracing digital zakat platforms as part of their religious practices.